Mo-Doped ultrafine VC nanoparticles confined in few-layer graphitic nanocarbon for improved electrocatalytic hydrogen evolution. Issue 21 (25th September 2020) - Cao, Liyun; Zhang, Ning; Feng, Liangliang; He, Danyang; Kajiyoshi, Koji; Li, Xiaoyi; Huang, Qian; Feng, Li; Huang, Jianfeng; Li, Ruizi
Abstract : Developing highly efficient, durable electrocatalysts based on cheap, non-precious metals for the hydrogen evolution reaction (HER) is still the key issue in the field of hydrogen economy. Abstract : Developing highly efficient, durable electrocatalysts based on cheap, non-precious metals for the hydrogen evolution reaction (HER) is still the key issue in the field of hydrogen economy. Herein, we report Mo-doped ultrafine VC nanoparticles confined in few-layer graphitic nanocarbon (Mo-VC@GC) by a facile one-step pyrolysis method. The as-prepared Mo-VC@GC exhibits enhanced electrocatalytic activity compared with the VC@GC counterpart, with a lower overpotential of 198 mV (VC@GC: 324 mV) to achieve a current density of 10 mA cm −2, a smaller Tafel slope of 169 mV dec −1 (VC@GC: 209 mV dec −1 ), along with outstanding long-term durability for at least 80 h, and ∼100% HER yield in 1 M KOH solution. The remarkable electrocatalytic performance of Mo-VC@GC can be attributed to the desirable electronic structures and crystallinity regulated by Mo-doping, the unique ultrafine VC nanostructures with abundant exposed active sites, and atomically thin graphitic nanocarbon with high conductivity as a support.